Effect of Sphaerosporella brunnea mycorrhizas on mycorrhization of Quercus ilex × Tuber melanosporum - Garcia-Montero, L. G.; Massimo, G. Di; Manjon, J. L.; García‐Cañete, J. (New Zealand Journal of Crop and Horticultural Science, 2008)
Abstract It is generally accepted that Sphaerosporella brunnea is a significant ectomycorrhizal contaminant in nurseries producing plants mycorrhized with various species of Tuber, and subsequently in truffières after outplanting. At the University of Alcalá, Spain, 397 small plants of Quercus ilex which were mycorrhized with Tuber melanosporum were inadvertently contaminated with S. brunnea, and this contamination was then monitored for 2 years. Sixty percent of the plants were contaminated and had S. brunnea ascomata on the surface of the container on one or several occasions. However, a Spearman test provided no evidence that S. brunnea mycorrhizas affected T. melanosporum mycorrhization whereas other contaminating ectomycorrhizal fungi significantly did. Therefore, it appears that S. brunnea is not detrimental to plants which are well mycorrhized with T. melanosporum.
doi: 10.1080/01140670809510231doi: 10.1080/01140670809510231The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: Black truffle; Mediterranean mushroom; Mycorrhizal fungi; mycorrhized contamination; Tuber melanosporum